Evaluation of personal protective equipment to protect health and safety in pesticide use - Aksüt, Güler; Eren, Tamer (Frontiers in Applied Mathematics and Statistics, 2024)
Introduction: Agriculture emerges as one of the most dangerous industries in the world, considering injury and illness rates. After the service sector in Turkey, the agricultural sector, which constitutes 20% of the general employment, comes. Health risks occur due to farmers' exposure to pesticides used to increase the quality and productivity of agricultural products through mouth, respiration, skin, and eyes. Pesticide use in Turkey is increasing; the annual average increase is estimated at 1.2%. Exposure to pesticides can be reduced by wearing personal protective equipment to protect against health and safety hazards.Objective: This study aimed to determine the importance of personal protective equipment with the multi-criteria decision-making method to prevent the risk of injury and disease resulting from pesticide use.The Analytical Hierarchy Process (AHP) method was used to find the weights of the criteria determined by expert opinion and literature review. The preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE) was used to rank personal protective equipment.Results: Personal protective equipment includes masks, gloves, overalls, safety shoes, glasses, and hats. The use of multi-criteria decision-making methods in health and safety in the agricultural sector will contribute to the literature.Emphasizing the use of personal protective equipment, especially when using pesticides, will increase the rate of using protective measures.